Digitalization of Business and Marketing Strategies to Increase Brand Awareness in the 4.0 Era: Strategi Digitalisasi Bisnis dan Pemasaran untuk Meningkatkan Brand Awareness di Era 4.0 - Sunarjo, Richard Andre; Baedowi, Hikmal; Rahardja, Untung; Ilham, Muhammad Ghifari; Parker, Jonathan (ADI Publisher, 2025)
The Industry 4.0 era marks a fundamental transformation in how businesses operate, with digitalization as a key catalyst in reshaping marketing strategies and branding. This study aims to examine the business and marketing digitalization strategies implemented by companies to increase brand awareness amidst technological disruption. By leveraging technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics, companies can expand brand reach, create more personalized communications, and increase real-time consumer engagement. The novelty of this study lies in its deep exploration of how these advanced technologies not only enhance operational efficiency but also significantly strengthen brand positioning by delivering more relevant, personalized, and integrated digital experiences to consumers. This study uses a mixed-method approach, namely a qualitative approach through case studies and a quantitative approach through a survey of industry players actively adopting Industry 4.0 technologies. The results show that digitalization not only improves operational efficiency but also strengthens brand positioning in the minds of consumers through relevant and integrated digital experiences. Furthermore, companies that successfully combine technological innovation with data driven marketing strategies tend to have stronger brand equity and high adaptability to market changes. These findings underscore the importance of investing in digital infrastructure and developing an innovative culture to strengthen brand awareness and sustainable business competitiveness.